Comportamiento defensivo de las abejas africanizadas (Hymenoptera: Apidae) en Dourados-MS, Brasil - Regina Faita, Márcia; Mattoso Colman Carvalho, Rita Maria; Vieira Alves-Junior, Valter; Chaud-Netto, José [UNESP] (My University, 2014)
African bees were introduced in Brazil in 1956, in an attempt to improve honey production. The accidental hybridization between African and European breeds originated africanized bees, which are very well adapted to the local climate. That bee poly-hybrid has an initial production of honey 70 % more than Europeans. However, African and africanized bees were much more defensive than European subspecies, which required the development of appropriate management techniques. Beekeepers in southern Mato Grosso do Sul learned to work with africanized bees. The aim of this study was to evaluate the defensive behavior of Africanized bees in Dourados MS, using a ball of black leather and artificial enemy. There were is recorded, the time to deliver the first bite, the time it takes to enrage (attack the enemy with great intensity), the distance from the pursuit of the enemy after the first attack and the number of bites left in the beanbag. The results indicate a significant concentration of colonies of bees with different intensity and defensive behavior, but similar to that presented by africanized bees in the 60/70, particularly in the region of Ribeirão Preto (SP). It appears, in terms of their defensive behavior, bees in the southern region of the state, did not suffer influence by bees of European origin.
Defensive behavior of africanized honeybees (Hymenoptera: Apidae) in Dourados-Mato Grosso do Sul, Brazil
Keywords: Africanized honeybees; Apis mellifera; Beekeeping; Defensive behavior